Architectural acoustics - Long, Marshall (Boston : Elsevier/Academic Press, 2014)
Architectural Acoustics, Second Edition presents a thorough technical overview of the discipline, from basic concepts to specific design advice. Beginning with a brief history, it reviews the fundamentals of acoustics, human perception and reaction to sound, acoustic noise measurements, noise metrics, and environmental noise characterization. In-depth treatment is given to the theoretical principles and practical applications of wave acoustics, sound transmission, vibration and vibration isolation, and noise transmission in floors and mechanical systems.
Historical introduction -- Fundamentals of acoustics -- Human perception and reaction to sound -- Acoustic measurements and noise metrics -- Environmental noise -- Wave acoustics -- Sound and solid surfaces -- Sound in enclosed spaces -- Sound transmission loss -- Sound transmission in buildings -- Vibration and vibration isolation -- Noise transmission in floor systems -- Noise in mechanical systems -- Sound attentuation in ducts -- Design and construction of multifamily dwellings -- Design and construction of office buildings -- Design of rooms for speech -- Sound reinforcement systems -- Design of rooms for music -- Design of multipurpose auditoria and sanctuaries -- Design of studios and listening rooms -- Acoustic modelling, ray tracing, and auralization.
Previous edition: 2005.
Includes bibliographical references (pages [911] - 929) and index.
Keywords: Architectural acoustics